2019
DOI: 10.1002/fld.4778
|View full text |Cite
|
Sign up to set email alerts
|

Simulating bubble dynamics in a buoyant system

Abstract: Multiphase flows are critical components of many physical systems; however, numerical models of multiphase flows with large parameter gradients can be challenging. Here, two different numerical methods, volume of fluid (VOF) and smoothed particle hydrodynamics (SPH), are used to model the buoyant rise of isolated gas bubbles through quiescent fluids for a range of Bond and Reynolds numbers. The VOF is an Eulerian grid-based method, whereas the SPH is Lagrangian and mesh free. Each method has unique strengths a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
(135 reference statements)
0
0
0
Order By: Relevance
“…Nguyen et al [21] used a geometrical VOF algorithm based on the piecewiselinear interface calculation (PLIC) to numerically investigate the dynamic behavior of bubble collapses, water jets, and pressure loads during the collapse of the bubble near walls and a free surface; the results showed a good agreement between the simulation and experiment of the bubble dynamics during the collapse process. Erin et al [22] used the SPH and VOF methods to simulate the rising of bubbles, and compared with previous experimental results, they concluded that both the VOF and SPH methods may be used to capture physically realistic transient and steady-state multi-phase systems; the SPH method could better capture the centroid of the bubble, while the VOF method better captured the rising velocity of the bubble.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nguyen et al [21] used a geometrical VOF algorithm based on the piecewiselinear interface calculation (PLIC) to numerically investigate the dynamic behavior of bubble collapses, water jets, and pressure loads during the collapse of the bubble near walls and a free surface; the results showed a good agreement between the simulation and experiment of the bubble dynamics during the collapse process. Erin et al [22] used the SPH and VOF methods to simulate the rising of bubbles, and compared with previous experimental results, they concluded that both the VOF and SPH methods may be used to capture physically realistic transient and steady-state multi-phase systems; the SPH method could better capture the centroid of the bubble, while the VOF method better captured the rising velocity of the bubble.…”
Section: Introductionmentioning
confidence: 99%
“…SPH is a meshless method. It is uniquely capable of representing the dynamic evolution of complicated geometries without additional algorithmic complication, such as those found in multi-phase flows [22]. When simulating fluid dynamics problems, the SPH method discrete the flow field into moving fluid micro clusters, which can be regarded as a combination of a series of molecules with the same properties [23].…”
Section: Introductionmentioning
confidence: 99%
“…The algebraic VOF method solves the volume fraction rate transport equation directly, without involving any geometric object. Existing researches show that the VOF method can depict complex interface structure and changes, and can be applied to the solution of two-phase flow [12] . Gim et al [13] presented an improved VOF model that based on smoothing functions, which effectively reduced the issue of spurious velocities.…”
Section: Introductionmentioning
confidence: 99%